PCR Detection of Coxiella Burnetii in Bovine Bulk Tank Milk Samples in Shiraz, Southern Iran - Samane Rahmdel; Maryam Sadat Moezzi; Negar Azimzadeh; Saeid Hosseinzadeh (International Journal of Nutrition Sciences, 2018)
Background: Q fever is a zoonosis caused by Coxiella burnetii, an obligate intracellular organism. In Iran, healthy cattle are the main reservoirs of these microorganisms. The consumption of milk and non-pasteurized dairy products is considered as a common way for transmission of infection from livestock to humans. Therefore, the present study aimed to determine the prevalence of C. burnetii in bovine bulk milk samples from dairy herds in Shiraz, southern Iran. Methods: A total of 100 bulk milk samples were collected from 20 traditional and 80 industrial dairy herds in Shiraz, southern Iran. The samples were then evaluated for the presence of the gene IS1111 using polymerase chain reaction (PCR) method. Results: Three out of 100 raw milk samples (3%) were contaminated with C. burnetii. The prevalence rate in traditional and industrial dairy herds was 10 % (two samples) and 1.2 % (one sample), respectively. Conclusion: The bovine raw milk can be a potential source of C. burnetii in Shiraz, southern Iran. Implementation of good hygienic practices on dairy farms, as well as the avoidance of consumption of raw milk and non-pasteurized dairy products is crucial to reduce the risk of infection transmission.